Peran Restrukturisasi Kredit Dalam Menurunkan Non Performing Loan Pada Kantor Cabang BRI Selayar - Nuryanti, Eka; Sari, A.Ratna; Ismail, Ismail (Patria Artha Journal of Accounting dan Financial Reporting, 2025)
This study aims to examine the impact of credit restructuring on the reduction of Non- Performing Loans (NPL) at PT. Bank BRI Cabang Selayar during the 2014–2023 period. A quantitative approach was employed using simple linear regression analysis. The data used are secondary data obtained from the bank’s internal reports. The results indicate that credit restructuring has a significant effect on decreasing NPL. This is evidenced by the coefficient of determination (R²) value of 0.751, meaning that 75.1% of the variation in NPL is explained by credit restructuring. The t-test also confirms a significant partial influence. Therefore, credit restructuring is proven to be an effective strategy in controlling problematic loans and maintaining asset quality. This research is expected to serve as a practical reference for credit risk management in the banking sector.